Identifikasi Dimensi E-Govqual Yang Harus Digunakan dalam Penelitian E-Government: Literatur Review - Dendy Iman Lesmana (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to identify the main dimensions in the e-GovQual model that are most relevant for use in evaluating e-Government services in Indonesia. The study was conducted through a systematic literature review method on ten national scientific articles published between 2018 and 2023. The articles were reviewed based on the use of e-GovQual dimensions in the context of implementing digital-based public services. The results of the analysis show five main dimensions that are most often used, namely Efficiency, Reliability, Responsiveness, Citizen Support, and Security. These findings are expected to be the basis for standardizing e-GovQual dimensions and contributing to the development of a more consistent and comprehensive digital public service quality evaluation framework.